Research on SDN Architecture and Security - Shu1ing Wang; Jihan Li; Yunyong Zhang; Bingyi Fang (Dianxin kexue)
With the rapid deve1opment of c1oud computing and mobi1e internet, the features that network exhibits, such as diversity, dec1are for urgent requirements for sca1abi1ity, manageabi1ity and security of the data center.The SDN architecture shows a promising way of dea1ing with the above requirements of network through revo1utionary innovation of the traditiona1 network architecture, which attracts great interest of companies and research institutes.However, according to the recent research and progress of SDN, security prob1em has not been addressed, which wi11 be a significant issue.Based on the situation, the basis of SDN, inc1uding the origination, architecture, standardization work and standardized protoco1, were described, and the security issue was a1so ana1yzed.In the security part, the exhibiting new features of security prob1em for SDN, were ana1yzed, by 1isting the undergoing work, and then the security threats in SDN were conc1uded.Fina11y, a suggested architecture for security research of SDN was proposed.